Association of White Matter Lesions and Outcome After Endovascular Stroke Treatment. (19th January 2021) - Luijten, Sven P.R.; Bos, Daniel; Compagne, Kars C.J.; Wolff, Lennard; Majoie, Charles B.L.M.; Roos, Yvo B.W.E.M.; van Zwam, Wim H.; van Oostenbrugge, Robert J.; Dippel, Diederik W.J.; van der Lugt, Aad; van Es, Adriaan C.G.M.; Dippel, Diederik; et al.
Abstract : Objective: To investigate the association between white matter lesions (WML) and functional outcome in patients with acute ischemic stroke (AIS) and the modification of the effect of endovascular treatment (EVT) by WML. Methods: We used data from the Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands (MR CLEAN) trial and assessed severity of WML on baseline noncontrast CT imaging (NCCT; n = 473) according to the Van Swieten Scale. Poststroke functional outcome was assessed with the modified Rankin Scale. We investigated the association of WML with functional outcome using ordinal logistic regression models adjusted for age, sex, and other relevant cardiovascular and prognostic risk factors. In addition, an interaction term between treatment allocation and WML severity was used to assess treatment effect modification by WML. Results: We found an independent negative association between more severe WML and functional outcome (adjusted common odds ratio [acOR] 0.77 [95% confidence interval (CI) 0.66–0.90]). Patients with absent to moderate WML had similar benefit of EVT on functional outcome (acOR 1.93 [95% CI 1.31–2.84]) as patients with severe WML (acOR 1.95 [95% CI 0.90–4.20]). No treatment effect modification of WML was found ( p for interaction = 0.85). Conclusions: WML are associated with poor functional outcome after AIS, but do not modify the effect of EVT. Classification of Evidence: Prognostic accuracy. This study provides Class II evidence that for patients with AIS, the presence of WML on baseline NCCT is associated with worse functional outcomes.